2011
DOI: 10.3807/josk.2011.15.1.090
|View full text |Cite
|
Sign up to set email alerts
|

12-year LIDAR Observations of Tropospheric Aerosol over Hefei (31.9°N, 117.2°E), China

Abstract: 12-year LIDAR observations of tropospheric aerosol vertical distribution using a Mie scattering LIDAR in Hefei (31.9°N, 117.2°E) from 1998 to 2009 are presented and analyzed in this paper. Characters of temporal variation and vertical distribution of tropospheric aerosol over Hefei are summarized from the LIDAR measurements. The impacts of natural source and human activities on the aerosol vertical distribution over Hefei could be seen clearly. Dust particles from the north in spring could affect the aerosol d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Hayashida et al [8] observed the volcanic disturbances in the stratospheric aerosol layer over Tsukuba, Japan. Some Chinese institutions such as the Anhui Institute of Optics and Fine Mechanics [9], Xi'an University of Technology [10], the Institute of Atmospheric Physics [11], and Lanzhou University [12] are also studying LIDAR systems to detect aerosols. Examples of studies are given by Yan et al [13], who observed the boundary layer structure and aerosol properties over Xi'an, Jinhuan et al [14], who analyzed the variation characteristics of the atmospheric aerosol optical depths and visibility in North China, and Huang et al [15], who detected the dust aerosol vertical structure.…”
Section: Introductionmentioning
confidence: 99%
“…Hayashida et al [8] observed the volcanic disturbances in the stratospheric aerosol layer over Tsukuba, Japan. Some Chinese institutions such as the Anhui Institute of Optics and Fine Mechanics [9], Xi'an University of Technology [10], the Institute of Atmospheric Physics [11], and Lanzhou University [12] are also studying LIDAR systems to detect aerosols. Examples of studies are given by Yan et al [13], who observed the boundary layer structure and aerosol properties over Xi'an, Jinhuan et al [14], who analyzed the variation characteristics of the atmospheric aerosol optical depths and visibility in North China, and Huang et al [15], who detected the dust aerosol vertical structure.…”
Section: Introductionmentioning
confidence: 99%
“…The seasonal aerosol vertical distribution over China has been studied using ground-based lidar observations at several sites (He et al, 2008;Huang et al, 2008a;Wu et al, 2011;Cao et al, 2013). The three-dimensional structure of aerosols over China has been estimated using the frequency of aerosol occurrence derived from CALIOP observations (Guo et al, 2016a).…”
mentioning
confidence: 99%
“…The diverse natural and anthropogenic aerosol sources as well as the geographical and meteorological conditions and transport pathways make China a unique natural laboratory for examination of seasonal dust particles, biomass burning, anthropogenic pollution and aerosols of mixed types . For example, spring dust particles originating from the source regions in the northwest of China are transported to the middle and upper troposphere (Wu et al, 2011; and to the downstream regions (Logan et al, 2010;. Long-range-transported particles typically are externally mixed with other aerosol constituents along their transport pathway (Logan et al, 2013;, because of atmospheric processing Zhang et al, 2008).…”
mentioning
confidence: 99%
“…Many equipments have been utilized to detect the optical properties of clouds and aerosol particles, such as nephelometer and sun-photometer, but LIDAR is a popular probe that can be used to scan the spacial physical properties in three dimensions, thereby reflecting clouds and aerosol particles distribution completely [5,6]. However, the original LIDAR signal and related retrieval parameters are affected by background noise and multiple scattering seriously.…”
Section: Introductionmentioning
confidence: 99%